Elaboration of French Thematic Comics Based on Creative Visual Media for A1 Level Reading Skills - Estella Aldina; Tri Hindri Hardini; Rachmadhany Ariessa (Raja Zulkarnain Education Foundation, 2025)
This study aims to elaborate and develop French language thematic comics based on creative visual media, namely comics titled Les Aventures d’Aurora et Eamon à Paris, which are specifically designed to improve reading skills at the A1 level and focus on the theme of tourism. This study uses a Research and Development (R&D) approach with instruments in the form of validation sheets for language experts and media experts. The research population consists of language and media experts, while the sample is one language expert and one media expert who provided product validation. Data were collected through expert judgment and open interviews, then analyzed using media feasibility percentage techniques and descriptive interpretation. The results show that the thematic comic product, in terms of language and content, is in the “Very Feasible” category with a score of 100% from the language expert. Qualitative input from the expert emphasized the need for a more dialogue-dominant narrative, the addition of a glossary, and complete product information. This comic presents practical scenarios relevant to real-world communication experiences, such as ordering food at a restaurant, ordering items, asking for directions, and shopping, through attractive illustrations and natural dialogue. This research concludes that the creative visual media-based thematic comic is an effective, relevant, interactive, and engaging innovative medium to support A1-level French reading learning.